1982
DOI: 10.1093/oxfordjournals.jbchem.a133688
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Glycosphingolipid, Asialo GM1, in Rat Immunocytes1

Abstract: One of the TLMA (rat T-lymphocyte-macrophage-associated antigens) was characterized as asialo GM1, Gal(beta, 1-3)GalNAc(beta, 1-4)Gal(beta, 1-1)-Cer by two assay methods using monospecific anti-asialo GM1 antibody, immunocytotoxicity testing and immunostaining. Nylon column-enriched T lymphocytes (non-adherent cells) were highly cytolyzed by anti-asialo GM1 antiserum and complement as compared with adherent cells (non T cells). Forty % of peritoneal exudate macrophages and 20% of granulocytes were also cytolyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Our finding that depletion of asialo-GM-1-positive cells confers resistance also implicates NK cells in the cascade of events leading to death. Nevertheless, the latter result must be interpreted with caution, because this phenotypic marker has also been reported to be on subsets of cells of the monocyte-granulocyte lineage (50). Together, the results suggest granulocyte involvement in triggering a cascade of inflammatory cytokines, resulting in progressive NO accumulation and ultimately precipitating host death.…”
Section: Discussionmentioning
confidence: 80%
“…Our finding that depletion of asialo-GM-1-positive cells confers resistance also implicates NK cells in the cascade of events leading to death. Nevertheless, the latter result must be interpreted with caution, because this phenotypic marker has also been reported to be on subsets of cells of the monocyte-granulocyte lineage (50). Together, the results suggest granulocyte involvement in triggering a cascade of inflammatory cytokines, resulting in progressive NO accumulation and ultimately precipitating host death.…”
Section: Discussionmentioning
confidence: 80%
“…This antiserum reduces NK cells in almost every organ in the body, including spleen 16,47 rather than just uNK cells. Moreover, anti-asialo GM1 also reacts with nonparenchymal liver cells, 48 T cells in mice 49 and rats, 50 as well as murine basophils 51 and monocytes 52 and rat granulocytes and macrophages. 50 The effect on various ILC subsets is poorly described.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, anti-asialo GM1 also reacts with nonparenchymal liver cells, 48 T cells in mice 49 and rats, 50 as well as murine basophils 51 and monocytes 52 and rat granulocytes and macrophages. 50 The effect on various ILC subsets is poorly described. Thus, we cannot conclude that the effects we observed were solely the result of NK or even uNK cell reduction.…”
Section: Discussionmentioning
confidence: 94%
“…In studies with anti-Gg4Cer (asialo-GMi) antisera, Gg4Cer was reported to be present on mature murine T cells (Stein et immunocytes of the rat (Momoi et al, 1982). Schwarting & Summers (1980) detected Gg4Cer in murine splenic T cells also by HPLC.…”
Section: Discussionmentioning
confidence: 99%